Energy recovery from pyrolysis of plastic waste: Study on non-recycled plastics (NRP) data as the real measure of plastic waste - Sharuddin, S.D.A.; Abnisa, F.; Daud, W.M.A.W.; Aroua, M.K. (Elsevier, 2017)
Oil produced from pyrolysis of plastics have been known for its higher calorific value than wood-based oil, in which comparable to conventional diesel. Even though many studies have been conducted on pyrolysis of plastics, the findings of those studies are not applied and reported yet according to the real portion of plastic waste. The real amount of plastic waste available is mainly derived from non-recycled plastics (NRP). NRP is defined as the plastic waste that remain in the recycling centers, which unable to be processed due to the certain restrictions. The amounts of NRP vary for each country based on daily applications. In this study, data of NRP in Malaysia, US, UK, as well as global were used to investigate the potential production of liquid fuel based on their different composition of plastic waste. Pyrolysis was conducted in a fixed bed reactor at 500 °C with nitrogen flow of 200 ml/min for 30 min reaction time. The addition of polystyrene (PS) into the NRP composition was also studied to evaluate the improvement of the liquid quality. Several important findings were discussed in this paper including some technical problems, features of the liquid product, characteristics of the by-products and potential energy recovery from NRP. The liquid product was analyzed by various methods such as FTIR, GCMS, elemental analysis and water content.